SOLVING DYNAMIC PLANNING PROBLEMS ON THE BASIS OF GROUP DECISION METHODS - Uskenbaeva, Р.К.; Kartbaev, Т.С.; Bayer, Д.; Togzhanova, К.О. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article discusses problems based on group methods of decision-making based on a multimodal approach to solving the problems of dynamic planning of Smart City development. In particular, the main tool for decision-making in the process of dynamic planning is a system of models and methods, which are the basis for creating the structure of the dynamic plan, optimizing the plan and finding the desired solution. Collective decision-making methods are used in the collective development of planning decisions, including in the context of solving the problems of dynamic planning of Smart City development and group decision-making, which requires the agreed decisions of several specialists.